2010 IEEE International Conference on Sustainable Energy Technologies (ICSET) 2010
DOI: 10.1109/icset.2010.5684431
|View full text |Cite
|
Sign up to set email alerts
|

Improving battery charging performance by using sinusoidal current charging with the minimum AC impedance frequency

Abstract: This paper aims to explore the optimal charging frequency of the LiFePO 4 battery by the analysis of the AC impedance. The experiments show that the optimal charging frequency is at the minimum AC impedance frequency. In such a condition, the LiFePO 4 battery charging time and charging efficiency are improved about 5.6% and 6.8%, respectively. In addition, the increased temperature of the battery can be slowed down about 6.3℃, the aging phenomenon of the LiFePO 4 battery can be reduced, and then the battery li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Figure 9 exhibits the Nyquist plot of a battery. A review of Figure 9 reveals that the battery internals are resistive, inductive and capacitive components, and the capacitive components of the Nyquist plot of a battery is presented in a semicircle case [25][26][27]. Figure 11 shows the flow chart of the presented SOC estimation approach for Li-ion battery proposed in this paper.…”
Section: Experimental Analysismentioning
confidence: 99%
“…Figure 9 exhibits the Nyquist plot of a battery. A review of Figure 9 reveals that the battery internals are resistive, inductive and capacitive components, and the capacitive components of the Nyquist plot of a battery is presented in a semicircle case [25][26][27]. Figure 11 shows the flow chart of the presented SOC estimation approach for Li-ion battery proposed in this paper.…”
Section: Experimental Analysismentioning
confidence: 99%
“…However, any form of pulse (involving t off ) comes with an additional operational cost incurred from the enhanced cell charging time. In addition to that, a combination of sinusoidal ripple with a constant DC potential in charging of a Li-ion battery at a minimum AC impedance frequency is demonstrated to result in a reduced charging time as well as increased charging efficiency, reduced heat load, and increased lifetime of the cell in comparison to the constant current–constant voltage charging. It is hypothesized that the sinusoidal perturbation reduces charge accumulation in the electrical double layer (EDL) and thereby limits the concentration polarization over the electrodes . In another study, it is also found that there is a certain frequency range of rippling for a specific concentration of electrolyte solution at which the roughness of the electrode surface is reduced, and beyond which it resembles the same as seen at constant DC plating.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in [187,188], the charging performance of LIB was improved by using SW charging at the frequency of 998 Hz which minimizes the AC impedance. Compared with CC-CV charging, SW charging in these works show enhanced performance regarding the charging time, charging efficiency, temperature build-up, and lifespan extension.…”
Section: Sinusoidal Wave Chargingmentioning
confidence: 92%
“…The parameters that define the waveform are the amplitude of DC bias, the amplitude of the SW, and the frequency of the SW. SW charging, also known as sinusoidal ripple current charging, is introduced to charge LIB at the frequency where the battery impedance reaches a minimum. This means the energy loss is minimized during charging and the energy transfer efficiency is maximized [187,188].…”
Section: Sinusoidal Wave Chargingmentioning
confidence: 99%